2008
DOI: 10.1007/s10681-008-9786-2
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic diversity in cold-tolerant peanut (Arachis hypogaea L.) germplasm

Abstract: Tolerance to low temperature is an important prerequisite for optimal performance of peanut (Arachis hypogaea L.) in a number of temperate peanut-growing environments. One hundred fifty-eight peanut accessions belonging to five botanical types, known to be tolerant to low temperature (12°C) at germination, were evaluated for phenotypic diversity for 15 morphological traits in the 2001 rainy season and for 15 agronomic and two seed quality traits in the 2001 rainy and 2001/2002 post-rainy seasons. Analysis of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…In practice, however, core collections composed of thousands of accessions are too large for use in breeding programs, and as a consequence breeders have preferred to focus on dozens to hundreds accessions. The result has been increased incorporation of useful genetic and phenotypic diversity into cultivated material, as illustrated for example in rice [54], chickpea [55 ], and groundnut [56]. 'Mini core' approaches focusing on only 1% of the collection [57,58] when whole collections are very large have been implemented for seven important crops at the International Crop Research Institute for the Semi-Arid Tropics (ICRISAT).…”
Section: Organizing Access To Diversitymentioning
confidence: 99%
“…In practice, however, core collections composed of thousands of accessions are too large for use in breeding programs, and as a consequence breeders have preferred to focus on dozens to hundreds accessions. The result has been increased incorporation of useful genetic and phenotypic diversity into cultivated material, as illustrated for example in rice [54], chickpea [55 ], and groundnut [56]. 'Mini core' approaches focusing on only 1% of the collection [57,58] when whole collections are very large have been implemented for seven important crops at the International Crop Research Institute for the Semi-Arid Tropics (ICRISAT).…”
Section: Organizing Access To Diversitymentioning
confidence: 99%
“…The selected low temperature tolerant lines can be used in crop improvement program to develop high yielding low temperature tolerant cultivars and to broaden the crop genetic base (Upadhyaya et al, 2001b). Additionally, 158 peanut core accessions belonging to five botanical types that are known to be tolerant to low temperature (12 °C) at germination, were evaluated for phenotypic diversity for 15 morphological, 15 agronomic, and two seed quality traits at Patancheru, India (Upadhyaya et al, 2009).…”
Section: Trait Discovery By Mining Core or Mini Core Collectionsmentioning
confidence: 99%
“…Ravindra et al (1990) reported that GG 2 in comparison to J11, JL 24 and TMV 10 has an inherent ability to produce more under drought stress occurring at any growth stage, while Ratnakumar and Vadez (2011) suggested that genotypes with lower leaf area may use water more sparingly under intermittent drought stress, which will have less damaging consequences for reproductive and pod development than genotypes having larger leaf area. Upadhyaya et al (2009) studied the phenotypic diversity in 158 cold tolerant peanut germplasm, which reported substantial diversity for base-temperature tolerance at germination (12°C, as used by Bell et al 1994) as well as for agronomic traits. The clustering pattern grouped the cold tolerant accessions into four clusters.…”
Section: Yield and Component Traitsmentioning
confidence: 99%